Conventional and alternative treatment approaches for Clostridium difficile Infection - Aljarallah, Khaild M (International Journal of Health Sciences, 2017)
Clostridium difficile-associated disease continues to be one of the leading health concerns worldwide. Clostridium difficile (C. difficile) is considered as a causative agent of nosocomial diarrhea that causes serious infection, which may result in death. The incidences of C. difficile infection (CDI) in developed countries have become increasingly high which may be attributed to the emergence of newer epidemic strains, extensive use of antibiotics and limited alternative therapies. The available treatment options against CDI are expensive and promote resistance. Therefore, there is urgent need for new approaches to meet these challenges. This review discusses the current understanding of CDI, the existing clinical treatment strategies and future potential options as anti-difficile agents based on the available published works.